Stability Results for Jungck-Kirk-Mann and Jungck-Kirk Hybrid Iterative Algorithms (Analysis in Theory and Applications, 2013)
In this paper, we introduce two hybrid iterative algorithms of Jungck-Kirk-Mann (J-K-M) and Jungck-Kirk (J-K) types to obtain some stability results for non-self mappings by employing a certain general contractive condition. Our results generalize and extend most of the existing ones in the literature.
Keywords: Stability result; Jungck-Kirk-Mann; Jungck-Kirk.